2020
DOI: 10.7224/1537-2073.2019-022
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Feasibility, and Efficacy of an Eccentric Exercise Intervention in People with Multiple Sclerosis with Ankle Contractures

Abstract: Background: The primary aim of this study was to investigate the safety and feasibility of an eccentric exercise program for people with multiple sclerosis (MS) who have ankle contractures, i.e. reduced ankle range of motion (ROM). Secondary aims were to explore the efficacy of eccentric exercise on ankle joint ROM and functional mobility. Methods: Five people with MS (3 females and 2 males, mean age 50.8 ± 9.4, duration of MS 7.6 ± years) completed two eccentric exercise training sessions (betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The large effect sizes reported in the present meta-analysis are greater than those reported after static stretching, and thus, eccentric exercise might be trialed more extensively in clinical conditions in which joint ROM is compromised and current therapies are ineffective. This suggestion is supported by clinically relevant improvements in ROM being reported after eccentric exercise in patients with contracture secondary to multiple sclerosis (68), emphasizing the potential for eccentric exercise to be an effective alternative therapy to enhance ROM in clinical populations. Furthermore, the present review examined passive rather than active ROM, and given that muscular strength is also frequently compromised in clinical conditions, measuring active ROM may highlight important functional (mobility) adaptations.…”
Section: Discussionmentioning
confidence: 87%
“…The large effect sizes reported in the present meta-analysis are greater than those reported after static stretching, and thus, eccentric exercise might be trialed more extensively in clinical conditions in which joint ROM is compromised and current therapies are ineffective. This suggestion is supported by clinically relevant improvements in ROM being reported after eccentric exercise in patients with contracture secondary to multiple sclerosis (68), emphasizing the potential for eccentric exercise to be an effective alternative therapy to enhance ROM in clinical populations. Furthermore, the present review examined passive rather than active ROM, and given that muscular strength is also frequently compromised in clinical conditions, measuring active ROM may highlight important functional (mobility) adaptations.…”
Section: Discussionmentioning
confidence: 87%
“…Only few studies have evaluated eccentric exercises in people with MS. Recently, a small pilot study demonstrated the feasibility, safety and efficacy of eccentric downhill walking in five people with MS affected by ankle contractures [ 37 ]. Additionally, eccentric strength training of the elbow flexors was proven to be feasible as well as beneficial for strength- and function-related parameters in people with MS with spasticity [ 38 ].…”
Section: Introductionmentioning
confidence: 99%